Births After Bariatric Surgery in the United States: Incidence, Obstetric Outcomes, and Reinterventions. Issue 4 (28th April 2023) - Chao, Grace F.; Yang, Jie; Peahl, Alex; Thumma, Jyothi R.; Dimick, Justin B.; Arterburn, David E.; Telem, Dana A.
Abstract : Objective: To characterize incidence and outcomes for bariatric surgery patients who give birth. Background: Patients of childbearing age comprise 65% of bariatric surgery patients in the United States, yet data on how often patients conceive and obstetric outcomes are limited. Methods: Using the IBM MarketScan database, we performed a retrospective cohort study of female patients ages 18 to 52 undergoing laparoscopic sleeve gastrectomy or Roux-en-Y gastric bypass from 2011 to 2017. We determined the incidence of births in the first 2 years after bariatric surgery using Kaplan-Meier estimates. We then restricted the cohort to those with a full 2-year follow-up to examine obstetric outcomes and bariatric-related reinterventions. We reported event rates of adverse obstetric outcomes and delivery type. Adverse obstetric outcomes include pregnancy complications, severe maternal morbidity, and delivery complications. We performed multivariable logistic regression to examine associations between birth and risk of reinterventions. Results: Of 69, 503 patients who underwent bariatric surgery, 1464 gave birth. The incidence rate was 2.5 births per 100 patients in the 2 years after surgery. Overall, 85% of births occurred within 21 months after surgery. For 38, 922 patients with full 2-year follow-up, adverse obstetric event rates were 4.5% for gestational diabetes and 14.2% for hypertensive disorders. In all, 48.5% were first-time cesarean deliveries. Almost all reinterventions during pregnancy were biliary. Multivariable logistic regression analysis showed no association between postbariatric birth and reintervention rate (odds ratio: 0.93, 95% confidence interval: 0.78–1.12). Conclusions: In this first national US cohort, we find giving birth was common in the first 2 years after bariatric surgery and was not associated with an increased risk of reinterventions. Clinicians should consider shifting the dialogue surrounding pregnancy after surgery to shared decision-making with maternal safety as one component.